2018
DOI: 10.1097/qad.0000000000001834
|View full text |Cite
|
Sign up to set email alerts
|

HIV transmission from infected CD4+ T cells to allogenic T and dendritic cells is inhibited by broadly neutralizing antibodies

Abstract: Overall, our results indicate that dendritic cells, in addition to CD4 T cells, are key cells that are efficiently infected by HIV and bNAbs are potent inhibitors of infection of both target cells. Future HIV prophylactic vaccine design should develop immune strategies able to prevent the infection of dendritic cells, in addition to the inhibition of CD4 T-cell infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Thus, it will be important to ascertain if a higher bn-mAb concentration will be necessary to prevent rectal transmission. Although the addition of seminal proteins did not impact VRC01 neutralization against cell-free Bal26 in the rectal explant challenge, further work will extend previous reports to address the role of seminal proteins in the neutralization of other viruses at mucosal sites (18), as well as the role of other antibodies in the prevention of infection from cell-associated viruses in semen (74,75).…”
Section: Discussionmentioning
confidence: 74%
“…Thus, it will be important to ascertain if a higher bn-mAb concentration will be necessary to prevent rectal transmission. Although the addition of seminal proteins did not impact VRC01 neutralization against cell-free Bal26 in the rectal explant challenge, further work will extend previous reports to address the role of seminal proteins in the neutralization of other viruses at mucosal sites (18), as well as the role of other antibodies in the prevention of infection from cell-associated viruses in semen (74,75).…”
Section: Discussionmentioning
confidence: 74%
“…Overall, our findings showed that HSP plays a pivotal role in recruiting CD11c+ MNPs at the apical side of the colonic epithelium and, when infected, serves as a vector for the virus to get in close contact with the colonic mucosa and relevant cells. Cavarelli and Baharlou, with two different techniques, highlighted how free HIV initially infects dendritic cells ( 14 , 43 ), and postulated that these cells are responsible for the subsequent viral spread to surrounding CD4+ T cells in the intestinal mucosa ( 44 , 45 ). In sexual transmission virions, however, are carried by semen and seminal fluid, and are rarely found in free form adjacent to colonic epithelial tissue.…”
Section: Discussionmentioning
confidence: 99%